Effect of Thermal Aging on Colour and Glossiness of U System Varnish-applied Laminated Parquet Layers - Ayata, Umit (2019)
Changes are reported in perpendicular and parallel glossiness, lightness (L*), red colour (a*) tone, and yellow colour (b*) tone due to thermal aging in beech (Fagus orientalis Lipsky), maple (Acer pseudoplatanus L.), northern red oak (Quercus rubra L.), American black walnut (Juglans nigra L.), and walnut (Juglans regia L.) wood coated with a UV system commonly used on laminated parquets. Coated samples were exposed to different thermal aging levels (30 °C for 30 days, 60 °C for 60 days, and 90 °C for 90 days). Colour and gloss were determined before and after the thermal aging processes. The L* decreased for all species with the thermal aging decreasing more for more intense processes. Variations of the a* and b* colour parameters depended on the species. The colour parameters changed for temperatures higher than 30 °C. In general, glossiness decreased proportionally to the severity of the thermal aging for all of the species studied.